Clarification on cost renewing of All Risk Insurance - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding clarification on cost renewing of All Risk (CAR) insurance for BRACU new campus project.